2012
DOI: 10.5899/2012/jfsva-00120
|View full text |Cite
|
Sign up to set email alerts
|

Computing the eigenvalues and eigenvectors of a fuzzy matrix

Abstract: Computation of fuzzy eigenvalues and fuzzy eigenvectors of a fuzzy matrix is a challenging problem. Determining the maximal and minimal symmetric solution can help to find the eigenvalues. So, we try to compute these eigenvalues by determining the maximal and minimal symmetric solution of the fully fuzzy linear system A X = λ X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Therefore from (8) and (9), it can be respectively shown that Based on similar arguments given in [4,49], set…”
Section: Symmetric Solution Of Fevpmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore from (8) and (9), it can be respectively shown that Based on similar arguments given in [4,49], set…”
Section: Symmetric Solution Of Fevpmentioning
confidence: 99%
“…However, the explicit form of the quantities α l, z ts and α u, z ts with respect to the different mentioned nature of the fuzzy matrix A(r) = { a ij (r)} will clearly be different. For further information, interested readers may consider the following papers [4,5,8,49]. Indeed in §5, numerical examples are illustrated for the different cases of the coefficient matrix.…”
Section: Symmetric Solution Of Fevpmentioning
confidence: 99%
See 1 more Smart Citation
“…The few existing studies on this topic provide partial solutions in a very restrictive framework, where the fuzzy matrices considered are subject to several constraints (see Buckley [1]; Salahshour and al. [2]). In addition to this, it should be stressed that those papers only treat fuzzy matrices with fuzzy coefficients, and they use the fuzzy arithmetic.…”
Section: Introductionmentioning
confidence: 99%
“…[5]; Salahshour and al. [2] studied the fuzzy eigenvalue and the fuzzy eigenvector by using the maximal and minimal symmetric spreads. Based on the definition of fuzzy Markov chain introduced by Avrachenkov and Sanchez [6], we address the same problem, but in a context where the fuzzy matrix has the same form as the one used in [6].…”
Section: Introductionmentioning
confidence: 99%